2019
DOI: 10.1111/jfb.14075
|View full text |Cite
|
Sign up to set email alerts
|

The omnivorous triggerfish Melichthys niger is a functional herbivore on an isolated Atlantic oceanic island

Abstract: This study evaluated the functional role of the highly generalist omnivore Melichthys niger in the remote St. Peter and St Paul's Archipelago (SPSPA), Brazil, where grazing herbivorous fishes are very scarce. We analysed patterns of distribution from zero to 30 m deep during three time intervals during the day and sampled different aspects of their feeding behaviour, including diel feeding rate, feeding substrate and diet. The density of M. niger increased with depth (26-30 m) and decreased by the end of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…While a similar number of species contributed to >90% of mass-standardised bites at both locations, there was evidence of greater behavioural flexibility in the less species rich Caribbean location. At our GBR location, Naso unicornis, a specialist macroalgal feeder (Choat et al 2002;Hoey and Bellwood 2009) dominated; however, the omnivorous triggerfish, Melichthys niger (Kavanagh and Olney 2006;Mendes et al 2019), was the dominant species at our Caribbean location. The identification of M. niger, in this context was particularly surprising (but see Randall 1967;Mendes et al 2019).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…While a similar number of species contributed to >90% of mass-standardised bites at both locations, there was evidence of greater behavioural flexibility in the less species rich Caribbean location. At our GBR location, Naso unicornis, a specialist macroalgal feeder (Choat et al 2002;Hoey and Bellwood 2009) dominated; however, the omnivorous triggerfish, Melichthys niger (Kavanagh and Olney 2006;Mendes et al 2019), was the dominant species at our Caribbean location. The identification of M. niger, in this context was particularly surprising (but see Randall 1967;Mendes et al 2019).…”
Section: Discussionmentioning
confidence: 68%
“…At our GBR location, Naso unicornis, a specialist macroalgal feeder (Choat et al 2002;Hoey and Bellwood 2009) dominated; however, the omnivorous triggerfish, Melichthys niger (Kavanagh and Olney 2006;Mendes et al 2019), was the dominant species at our Caribbean location. The identification of M. niger, in this context was particularly surprising (but see Randall 1967;Mendes et al 2019). To-date, evidence from the Caribbean generally suggests that the sparisomatine parrotfishes dominate macroalgal removal (Sparisomatina; Bellwood et al 2019b;Siqueira et al 2019b) with secondary roles attributed to Acanthurus surgeonfishes (e.g.…”
Section: Discussionmentioning
confidence: 68%
“…Furthermore, while some of the previous studies have highlighted the contribution of some of these herbivores to limit the abundance of invasive algae, our findings suggest that non-strict herbivores could also potentially have a similar, albeit less important contribution. Therefore, these findings provide another example on the important role that omnivorous fish species might have on marine ecosystems, where they have been reported to play a key role on the coralalgae equilibrium in coral reefs from several regions (Bellwood et al, 2006;Tebbett et al, 2020), and to become an important link between primary producers and higher trophic levels in rocky reefs (Mendes et al, 2015(Mendes et al, , 2019. In our case, given the high amounts of C. cylindracea found in some specimens and considering that omnivorous sparid fishes dominate the shallow rocky infralittoral habitats in the Mediterranean Sea (García-Rubies, 1997;Sala and Ballesteros, 1997;García-Charton et al, 2004;Coll et al, 2013) with abundances of up to 60 individuals per 250 m 2 and biomasses of more than 40 g/m 2 (García-Rubies and Zabala, 1990;Sala and Ballesteros, 1997;Di Franco et al, 2009;Guidetti et al, 2014;Coll, 2020), it seems that they could potentially have some impact on the abundance of C. cylindracea.…”
Section: Discussionmentioning
confidence: 79%
“…Until now, assessments on the role of herbivory as a limiting factor for macroalgae invasion have mainly considered strictly herbivorous species (e.g., Lyons and Scheibling, 2008;Britton-Simmons et al, 2011;Enge et al, 2017;Noè et al, 2017;Caselle et al, 2018), reporting contrasting results depending on the assemblage and the invasive species considered (e.g., Sumi and Scheibling, 2005;Steinarsdóttir et al, 2009;Tomas et al, 2011b;Nejrup et al, 2012;Enge et al, 2017;Caselle et al, 2018). Actually, considering that omnivores have been reported to influence macroalgae and phytobenthos abundance in different ecosystems around the globe (Bellwood et al, 2006;Mendes et al, 2015Mendes et al, , 2019Tebbett et al, 2020), and that they can act as important functional groups, for instance, in the reversal of community phase-shifts in coral reefs (Bellwood et al, 2006;Tebbett et al, 2020), we pose that they could also potentially consume invasive alga species and influence their abundance. Therefore, to improve our understanding on the ecological role of omnivorous fishes and to assess whether they can contribute to the resistance of native habitats against invaders, it is necessary to assess invasive alga consumption by these species.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, Dance (2017) recorded crabs, bivalves and gastropods as the major component of diet in B. capriscus from north-west Gulf of Mexico with unidentified partially digested invertebrates and fishes. However, Mendes et al (2019) reported that algal matter dominated (55.8%) in the diet of Melichthys niger from an isolated Atlantic oceanic island. Balistes capriscus inhabiting in the south-eastern USA was seen to consume barnacles, gastropods (pelagic pteropods) and decapods (unidentified shrimps) (Goldman et al, 2016).…”
Section: Food and Feedingmentioning
confidence: 99%